Correlating electronic properties with M-site composition in solid solution TiyNb2-yCTx MXenes. (1st January 2023) - Yang, Yizhou; Han, Meikang; Shuck, Christopher E; Sah, Raj K; Paudel, Jay R; Gray, Alexander X; Gogotsi, Yury; May, Steven J
Abstract: High electrical conductivity is desired in MXene films for applications such as electromagnetic interference shielding, antennas, and electrodes for electrochemical energy storage and conversion applications. Due to the acid etching-based synthesis method, it is challenging to deconvolute the relative importance that factors such as chemical composition and flake size contribute to resistivity. To understand the intrinsic and extrinsic contributions to the macroscopic electronic transport properties, a systematic study controlling compositional and structural parameters was conducted with eight solid solutions in the Ti y Nb2− y CT x system. In particular, we investigated the different roles played by metal (M)-site composition, flake size, and d -spacing on macroscopic transport. Hard x-ray photoemission spectroscopy and spectroscopic ellipsometry revealed changes to electronic structure induced by the M-site alloying. Consistent with the spectroscopic results, the low- and room-temperature conductivities and effective carrier mobility are correlated with the Ti content, while the impact of flake size and d -spacing is most prominent in low-temperature transport. The results provide guidance for designing and engineering MXenes with a wide range of conductivities.